Analisis daya saing komoditas kedelai di sentra produksi=(The Analysis the Competitiveness on Soybean Commodities in Cente - Soetrion Soetrion (Agro Ekonomi, 2004)
The main objectives of this paper are to investigate the government pric policy and its implication on the soybean farming competitiveness; and formu late policy alternatives to enhance the soybean commodity competitiveness i agro-industry sector. This study was conducted in soybean farming center at th Grajagan Village, Purwohardjo district, Banyuwangi regency. The site was Se lected based on the Location Quotient analysis. The research method.used i this study is Policy Analysis Matrix (PAM). The result of the study are as follows price policy of the soybean commodity system could produce production surplu hy 4 %. This surplus enables producers to compete in the domestic market. 7 face the free trade, this policy could only achieve potential income of farming b 77 % and tempe-tofu industry by 91 %. With the current price policy, the soybea commodity still has an advantage showed by the comparative advantage wit the DRCsodaivalue of Rp 6.253 and domestic resource cost coefficient (CDRCria value of 0.67 as well as competitive advantage with the value of R, 6.888 and the domestic resource cost coefficient (CDRC,,,,,,,,,) value of 0.74. Gal eminent price policy for soybean commodity does not provide incentive for th development of the tempe-tofu industry. This is shown by the Effective Protectio and Profitability Coefficients (EPC and PC) which is less than 1 and the nega tive Subsidy Ratio to Producers (SRP) for both farming and agro-industry. An other policy alternative for increasing the soybean commodity competitivenes in agro-industry development is by increasing the productivity and output pric protection at the farmers level. Another policy alternative is the subsidy of fertil izer and pesticide whenever other countries have the same policy.